ҚАЗАҚ ТИЛИНДЕГИ САЛТ-ДӘСТҮРЛЕРГЕ БАЙЛАНЫСЛЫ ЭТНОФРАЗЕОЛОГИЗМЛЕР - Адилова, Г.А. (НАУКА и ОБЩЕСТВО, 2022)
In the language of each nation has ethnophraseologisms associated with national customs and traditions. They were formed and passed down from generation to generation in connection with the attitude of the population to the environment, to life, beliefs and have reached our days. The article makes a linguistic analysis of ethnophraseologisms that have developed in connection with the family traditions of the Kazakh people, spiritual customs, rituals such as "besik kuda", "kiyit kiygiziw", "toy baslar" and so on.
Keywords: урф-одат; анъана; маънавий маданият; этнофразеологизм